HUBUNGAN POSISI DUDUK DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEKERJA PABRIK DUPA MAHADEWA BAGIAN PERCETAKAN DI DESA EKASARI - Anggraeni, Komang Putri; Antari, Gusti Ayu Ary; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023, 2024)
One of the most common health issues with the potential to cause a wide range of complications is low back pain complaints. Many workers don't realize they are sitting in an unhealthy position and continue to do so as they go about their daily routines. This is one of the leading causes of back pain. Negative effects on employees due to back pain include lower productivity on the job, deteriorating health, and increasing muscle pain complaints. The aims of this study is to correlate employees' sitting postures with their risk of developing lower back pain on the job at the Mahadewa Incense Factory. This type of research is a descriptive correlational with a cross-sectional design. The Rapid Upper Limb Assessment (RULA) low back pain questionnaire and observation sheet are the measuring tools used. Sampling was carried out using a total sampling technique with 45 respondents from all workers in the printing sector at the Mahadewa Incense Factory. Analysis test results using Spearman showed that the majority of workers are in the late teens to late elderly range who live a good lifestyle and when doing work, they are at low risk or in the "normal position" category when sitting while working. This suggests that there is no correlation between employees' sitting positions and their levels of stress during the workday at Mahadewa Incense Factory in Ekasari Village (p>0,05). The workers are advised to proceed the ergonomic sitting position and if the pain was felt, they were suggested to evaluate and make chages to their sitting position.